2016
DOI: 10.1186/s13018-016-0391-0
|View full text |Cite
|
Sign up to set email alerts
|

Local application of rapamycin reduces epidural fibrosis after laminectomy via inhibiting fibroblast proliferation and prompting apoptosis

Abstract: BackgroundEpidural fibrosis is a common complication after laminectomy. It is associated with intractable lower back pain and additional complications. To date, no study has evaluated whether the local application of rapamycin (RAPA) can inhibit fibroblast proliferation and reduce epidural scar adhesion after laminectomy. The results of the present study showed that the local application of RAPA reduces epidural fibrosis after laminectomy in rats.MethodsIn this study, 32 male Sprague-Dawley rats were randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 42 publications
(31 reference statements)
2
16
0
Order By: Relevance
“…Local immune response is considered critical for each type of post‐operative skeletal fibrosis and some immunosuppressant drugs used to prevent post‐operative skeletal fibrosis have achieved success, including rapamycin, tacrolimus, pimercrolimus, azithromycin, methotrexate and cyclosporin A . Results showed that they could prevent post‐operative skeletal fibrosis by inhibiting fibroblast proliferation, suppressing interleukin 2 (IL‐2) and TGF‐β1 expression, regulating miR‐429 and RhoE expression and activating autophagy and the ER stress signaling pathway …”
Section: Current Therapies For Post‐operative Skeletal Fibrosismentioning
confidence: 99%
“…Local immune response is considered critical for each type of post‐operative skeletal fibrosis and some immunosuppressant drugs used to prevent post‐operative skeletal fibrosis have achieved success, including rapamycin, tacrolimus, pimercrolimus, azithromycin, methotrexate and cyclosporin A . Results showed that they could prevent post‐operative skeletal fibrosis by inhibiting fibroblast proliferation, suppressing interleukin 2 (IL‐2) and TGF‐β1 expression, regulating miR‐429 and RhoE expression and activating autophagy and the ER stress signaling pathway …”
Section: Current Therapies For Post‐operative Skeletal Fibrosismentioning
confidence: 99%
“…are the prominent experimental materials. 2,[4][5][6][7]9,12,13,15,16,18,19 Some of these materials have been used clinically. Although most studies are animal experiments, as of today, satisfactory clinical studies confirming that these materials can help attenuate fibrosis in clinical applications have not been achieved yet.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were cultured at 37˚C in 5% CO 2 with DMEM (Gibco; Thermo Fisher Scientific, Inc.), supplemented with 15% FBS (Gibco; Thermo Fisher Scientific, Inc.) and 1% penicillin & streptomycin (Gibco; Thermo Fisher Scientific, Inc.). A total of 1x10 6 fibroblasts were seeded in petri dishes with a variety of specifications overnight until a confluence of 70% was attained; then the dishes were washed twice with PBS. One third of the fibroblasts were set as the lY group and were treated with the Pi3K inhibitor lY294002 (Medchemexpress) diluted in dimethylsulfoxide to 50 µM for 24 h. Another third of the fibroblasts were treated with siRNA for knockdown or lentiviral vectors for overexpression.…”
Section: Histological Analysis Of Hematoxylin and Eosin (Hande)mentioning
confidence: 99%
“…Fibroblasts in the overexpression and scramble control group were cultured until they reached 70% confluence. Subsequently, 1x10 6 fibroblasts/well were transfected with 2x10 7 Tu (multiplicity of infection of 20) laminin α5 GV418 lentiviral vector or GV418 scramble control empty vector overnight in the presence of 2 mg/ml polybrene (Gibco; Thermo Fisher Scientific, Inc.) and then replaced with fresh complete medium. After 48 h-transfection at 37˚C, cells were cultured in puromycin (Sigma-aldrich; Merck KGaa) at a concentration of 2 µg/ml for 72 h for the preliminary screening to eliminate non-transfected cells.…”
Section: Histological Analysis Of Hematoxylin and Eosin (Hande)mentioning
confidence: 99%
See 1 more Smart Citation